The Magnetic Compass of Birds: The Role of Cryptochrome - Wiltschko, Roswitha; Nießner, Christine; Wiltschko, Wolfgang (Frontiers in Physiology, 2021)
The geomagnetic field provides directional information for birds. The avian magnetic compass is an inclination compass, not using the polarity of the magnetic field, but the axial course of the field lines and their inclination in space. It works in a flexible functional window, and it requires short-wavelength light. These characteristics result from the underlying sensory mechanism based on radical pair processes in the eyes, with cryptochrome suggested as receptor molecule. The chromophore of cryptochrome, FAD, undergoes a photocycle, where radical pairs are formed during photo-reduction as well as during re-oxidation; behavioral data indicate the latter is the crucial ones for detecting magnetic directions. Five types of cryptochromes are found in the retina of birds: Cry1a, Cry1b, Cry2, Cry4a and Cry4b. Because of its location in the outer segments of the UV cones with their clear oil droplets, Cry1a appears to be the most likely receptor molecule for magnetic compass information.